Analisis Penerapan Kurikulum Kerangka Kualifikasi Nasional Indonesia (KKNI) pada Prodi S1 Pendidikan Ekonomi Universitas Negeri Surabaya dan STKIP PGRI Jombang - Nur Lita Faridah; Luqman Hakim; Muhammad Fahmi Yafi (Edunusa: Journal of Economics and Business Education, 2021)
This study aims to compare two applications of the KKNI curriculum used by the two Economic Education Study Programs, Unesa and STKIP PGRI Jombang concerning the agreement made by the Indonesian Economic Educator Professional Association (Aspropendo). This research is a descriptive study that uses a qualitative approach. Data collection in this study uses observation, interview, and documentation techniques. The results of this study reveal that there are several differences and similarities between the implementation of the curriculum in the two study programs, this can be seen in the curriculum preparation, implementation, and evaluation. The advantages of implementing the KKNI curriculum can be seen in the courses that are characteristic of each university. Meanwhile, the deficiencies need to be improved. The researcher hopes that this research can be used as a reference and also as a consideration for other Economic Education Study Programs in compiling an IQF-based curriculum concerning the agreement made by Aspropendo.